LINGUACULTURAL FEATURES OF FALSE COMMUNICATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This thesis highlights linguacultural aspects of false communication. There are different views of false communication and portraying lying characters in literary works various cultures.